Preparation of activated carbon by chemical activation using Z. Spina-Christi fruits nuclei as raw material - Jabbar, Susan F. (University of Thi-Qar Journal of Science, 2014)
The research work involves preparation and study of the adsorption characteristics of activated carbon to remove dyes from aqueous solutions . Z. Spina-Christi fruits nuclei were processed chemically using Phosphoric acid as chemical activator. The parameters (such as initial pH , contact time,..etc) affecting the adsorption capacity of activated carbon toward dyes removal from aqueous solutions were investigated